Shoulder Instability – Results of Different Methods of Treatment - Matev B. (Sciendo, 2019)
The aim of this study is to present results after different procedures of surgical treatment of the unstable shoulder joint: arthroscopic stabilization; arthroscopic stabilization followed by the operative technique by Matev; the Latarjet procedure in cases with the presence of bone defects. From 2004 to 2017 291 patients aged between 15 and 35 years were operated at the University Hospital “Prof. B. Boychev”, Medical University − Sofia. 247 patients had anterior and 44 − combined shoulder instability. 173 of the patients were active athletes practicing different disciplines. The average age at the time of the first dislocation was 17 years. In 172 patients, the first dislocation occurred without significant trauma, 124 of them had anterior shoulder instability and 48 – combined shoulder instability. In 120 patients with anterior dislocations, there was history of a serious injury during the first accident. The number of dislocations varied between ten and fifteen in all patients. For the same period, 45 patients with significant bone defects requiring open surgery (Latarjet procedure) were operated. Among the patients with bone defects, the dislocations were between 8 and 30 before the first examination. There were 11 patients, who had undergone previous surgery in different hospitals and different number of relaxations after surgery were found. The data were evaluated radiographically and clinically. Functionally, the patients recovered according to a well-established protocol of physiotherapy and the external rotation regained the full range of motion. The patients were able to return to their sports activity. The successful results in all patients show that these combined operative techniques can be the method of choice in the treatment of a greater number of dislocations of the shoulder, especially in people who seek to quickly return to active sport activities.